2017
DOI: 10.5758/vsi.2017.33.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Initial Clinical Experience with the Endologix AFX Unibody Stent Graft System for Treating Patients with Abdominal Aortic Aneurysms: A Case Controlled Comparative Study

Abstract: PurposeThe newly designed unibody AFX endograft system for endovascular aortic aneurysm repair is the only graft with anatomical fixation to the aortic bifurcation in comparison to most other grafts that use the infrarenal neck as the main fixation point. The aim of this study was to assess the preliminary results of the AFX stent-graft system used with infrarenal aortic component and compare them with those obtained in patients treated with a well established endograft of the same material and pure infrarenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The type II EL incidence is comparable to reports by other researchers using the same stent graft system. For example, Kouvelos et al reported a type II EL rate of 10% after a median follow-up of 23 months when using the AFX stent graft, whereas Welborn et al found a rate of 5.7% at 9-month follow-up [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The type II EL incidence is comparable to reports by other researchers using the same stent graft system. For example, Kouvelos et al reported a type II EL rate of 10% after a median follow-up of 23 months when using the AFX stent graft, whereas Welborn et al found a rate of 5.7% at 9-month follow-up [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This graft stiffness is also a problem in cases of wide beta angulation. In our experience, the telescopic technique of the AFX2 stent can be used to overcome these limitations, although more research is needed [21].…”
Section: Discussionmentioning
confidence: 99%
“…The AFX bifurcated unibody aortic endograft (Endologix, Irvine, California)-FDA-approved for EVAR-has also been successful in treating TASC D AIOD lesions with primary and assisted primary patency rates of 91 and 97% at 1 year, respectively (Figure 3) [48]. Unlike traditional modular bifurcated aortic endografts with fixation points at the infrarenal proximal aortic neck, the AFX is fixed at the aortic bifurcation [49]. Furthermore, it is delivered through a 17-Fr ipsilateral and a 9-Fr contralateral sheath facilitating advancement and deployment in heavily calcified, small-caliber iliac arteries [49].…”
Section: New Generation Of Aortic Endograftsmentioning
confidence: 99%
“…Unlike traditional modular bifurcated aortic endografts with fixation points at the infrarenal proximal aortic neck, the AFX is fixed at the aortic bifurcation [49]. Furthermore, it is delivered through a 17-Fr ipsilateral and a 9-Fr contralateral sheath facilitating advancement and deployment in heavily calcified, small-caliber iliac arteries [49]. In a recent study, the AFX unibody stent was successfully used in the treatment of TASC C/D lesions in patients with concomitant AAA [50].…”
Section: New Generation Of Aortic Endograftsmentioning
confidence: 99%